Keterampilan Manajer Sekolah dalam Mewujudkan Sekolah Efektif di SMP Negeri 1 Jepara - Rahayu, Endah Sri; Yuliejantiningsih, Yovitha; Sudana, I Made (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
This research focuses on: (1) the conceptual skills of the principal in creating an effective school at SMP Negeri 1 Jepara; (2) the human relations skills of the principal in creating an effective school at SMP Negeri 1 Jepara; (3) The technical skills of the principal in creating an effective school at SMP Negeri 1 Jepar. This research approach is qualitative research by extracting data using the WOS method (interviews, observation and documentation). Use of data analysis with data triangulation. Based on the research results, it was found that the principal of SMP Negeri 1 Jepara has the following managerial skills: (1) concept skills (analysis ability, ability to think rationally, ability to form concepts; (2) human relations skills (communication skills, motivation skills, trust building skills) and (3) the principal's technical skills (ability to apply knowledge, skill in using methods, ability to utilize infrastructure) at SMP Negeri 1 Jepara work well in creating an effective school (professional leadership, realizing vision, mission and shared goals, effective management strategies effective and create a conducive school culture. This research suggests that school principals can understand and develop the leadership skills of school principal managers in creating effective schools and for future research research can be carried out on the influence of school manager leadership dimensions on effective schools.